Diversity of Sand Flies (Diptera: Psychodidae) in Endemic Focus of Visceral Leishmaniasis in Azar Shahr District, East Azarbaijan Province, North West of Iran - Teimour Hazratian; Hasan Vatandoost; Mohammad Ali Oshaghi; Mohammad Reza Yaghoobi-Ershadi; Esmael Fallah; Sayena Rafizadeh; Mohammad Reza Shirzadi; Mansoreh Shayeghi; Kameran Akbarzadeh; Yavar Rassi (Tehran University of Medical Sciences, 2016)
Background: There are nearly 1000 species of Phlebotomine sand flies in 6 genera, of which only two, Phlebotomus in the old world and Lutzomyia in the new world are medically important. Globally, leishmaniasis prevalent in 98 countries and affects estimated 12 million people with almost two million new cases per year. Some rural areas of Azarshahr District in East Azarbaijan Province have been reported to be endemic for visceral leishmaniasis. This study is the first attempt to determine the species diversity and density in a new focus of visceral leishmaniasis in Azarshahr District, East Azarbaijan Province, Iran. Methods: Sand flies were collected form indoor and outdoor biweekly using sticky traps. Diversity index of the collected sand flies within different villages were estimated by the Shannon-Weaver. Results: The activity of the sand flies extended from April to October with one peak in August. Diversity of sand flies within study area were estimated as 0.917, 1.867, 1.339, 1.673, and 1.562 in Almalodash, Jaragil, Segaiesh, Amirdizaj, and Germezgol Vvillages, respectively. Conclusion: Identifying the diversity and seasonal abundance of the collected species is of importance for prediction of the period of maximum risk for leishmaniasis transmission and for the successful implementation of a control program. Species diversity is one of the most important factors in ecological studies.